2019
DOI: 10.1111/dmcn.14347
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for perinatal arterial ischaemic stroke: a large case–control study

Abstract: Aim To identify maternal, obstetric, and neonatal risk factors related to perinatal arterial ischaemic stroke (PAIS) diagnosed within 28 days after birth and to understand the underlying pathophysiology. Method For case and control ascertainment, we used active surveillance in 345 paediatric hospitals and a population‐based perinatal database for quality assurance of hospital care. We analysed complete cases of PAIS using logistic regression. Multivariate analysis was guided by a directed acyclic graph. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 35 publications
6
48
0
3
Order By: Relevance
“…By multiplying the risk of NAIS by 10, Sorg et al. reveal that chorioamnionitis far outweighs other identified determinants . Furthermore, perinatal inflammation was a constant independent risk factor in previous case–control studies of NAIS .…”
mentioning
confidence: 99%
“…By multiplying the risk of NAIS by 10, Sorg et al. reveal that chorioamnionitis far outweighs other identified determinants . Furthermore, perinatal inflammation was a constant independent risk factor in previous case–control studies of NAIS .…”
mentioning
confidence: 99%
“…However, some evidence supports our nding that newborns with CSVT often present later with unspeci c signs within the rst week of life [24]. In a recent paper we discussed risk factors for AIS and identi ed an important role for prenatal risk factors [25]. Perinatal asphyxia in AIS might as well be a consequence of AIS.…”
Section: Discussionmentioning
confidence: 55%
“…Due to the efficient anastomosis of the circle of Willis in pups, our experimental design requires adding hypoxic stress to the ischemia‐induced by RCCA ligation to trigger a stroke. However, the triple‐hit (namely, bacterial (LPS) component exposure plus focal ischemia plus global hypoxia) used in our experimental design is relevant with the most prevalent causal pathway of human NAIS featured by the sequence of chorioamnionitis (Giraud et al, 2017; Martinez‐Biarge et al, 2013; Sorg et al, 2019), peripartum asphyxia identified in up to 26% of NAIS (Fluss et al, 2019; Martinez‐Biarge et al, 2013; Michoulas et al, 2011; Ramaswamy, Miller, Barkovich, Partridge, & Ferriero, 2004; Sorg et al, 2019), and arterial occlusion of the carotid tree (Fluss et al, 2016; Husson et al, 2016; Kirton et al, 2011; Suppiej et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal arterial ischemic strokes (NAIS) affects up to 1–2/6,000 newborns and results in lifelong sequelae, such as cerebral palsy and epilepsy, as well as cognitive and behavioral impairments (Dunbar & Kirton, 2018; Fluss, Dinomais, & Chabrier, 2019; Giraud, Guiraut, Chevin, Chabrier, & Sébire, 2017). Clinical studies show that perinatal infection/inflammation—often due to chorioamnionitis—is the main independent risk factor of NAIS (Giraud et al, 2017; Martinez‐Biarge, Diez‐Sebastian, Wusthoff, Mercuri, & Cowan, 2013; Sorg et al, 2019). To date, no controlled clinical trials have addressed the safety and efficacy of hypothermia (HT) in NAIS (Austin, Shanmugalingam, & Clarke, 2013; Harbert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%